The opportunities of socially disadvantaged people to be occupied in labour market - Gruževskis, Boguslavas (Socialinė teorija, empirija, politika ir praktika, 2003)
The results of the research on the opportunities of socially disadvantaged people to be occupied in labour market are presented in the paper. The survey method was used in order to obtain data. The goal of the research was to explore the incomes, living conditions, needs for social services, and attitude towards occupation in labour market. The special attention was paid to the attitude to participate in different occupational forms – paid job, unpaid job, and public works. The reasons not to be occupied in labour market and the need for vocational training were analysed also.
Keywords: Socially disadvantaged people; Occupation; Vilnius